Densely packed, highly strain sensitive carbon nanotube composites with sufficient polymer penetration. (March 2020) - Liu, Xiaohua; Wei, Baochun; Farha, Farial Islam; Liu, Wei; Li, Wuzhou; Qiu, Yiping; Xu, Fujun
Abstract: The nano-porous structure of CNT film severely limits the penetration of polymer resin for advanced composites. To solve this critical issue, we propose a method which could not only uniformly infiltrate resin into CNT films along thickness direction but also ensure sufficient polymer penetration for the fabrication of CNT film/epoxy composites. The resultant composites revealed an outstanding improvement of 352% and 664% accordingly for tensile strength and Young's modulus. It also showed 8 times enhancement of tensile toughness compared to that of the pristine CNT film. Furthermore, the high sensitivity (gauge factor 4.6) with a linear piezo resistive response within a large strain ( 5%) and the stable sensing reversibility, demonstrated the excellent strain sensing properties of the produced composites. Therefore, our study innovatively proposes this vacuum-assisted filtration method to obtain the strong fibre-matrix interface interaction inside the dense CNT assemblies as well as other nanomaterials.